Primary Health Care and Occupational Health. Results from a survey on general practitioners of the Province of Monza and Brianza - Riva, Michele Augusto; Belingheri, Michael; Castiglioni, Elisabetta; Bonazzi, Chiara (La Medicina del Lavoro, 2017)
Background: The World Health Organization has been asking for greater collaboration between occupational medicine and primary care for many years. Objectives: To investigate the knowledge of general practitioners (GPs) working in a province of Lombardy about occupational health issues and their experiences with work-related problems among their patients. Methods: Data were collected by telephone interview to GPs, using a 25-item questionnaire. Results: 111 GPs answered to the questionnaire (66.5% of the sample). Only 34.2% of the doctors knew the current regulation of occupational medicine in Italy. The GPs considered that the main work-related disease among their patients were musculoskeletal disorders and work-related stress. 90% of doctors stated to have sent at least one of their patients to an occupational medicine clinic. Only 9% declared to have notified at least one occupational disease. Among GPs who suggested how to improve the relationship between primary care and occupational medicine, 44% proposed training courses on this topic. Only 16.2% said to have attended an occupational health course during university studies. Conclusions: Italian GPs have poor knowledge about occupational medicine and they also have difficult relationships with occupational health physicians. Initiatives to improve cooperation between these two sectors are desirable.